Evaluation of Organic Treatments for Enhanced Bioremediation of Crude Oil Impacted Soil in Bayelsa State, Nigeria - Asuka, Ebiye; Hyginus, Oku (Journal of Sustainability and Environmental Management, 2023)
The aim of this study was to evaluate organic treatments for enhanced bioremediation of crude oil impacted soil in Bayelsa State, Nigeria. Koroama community in Gbarain clan, Yenagoa local government area, Bayelsa State, Nigeria was randomly selected for the study. The experimental research design was adopted for this study, which was carried out for 28 days. The required soil samples were collected at a depth of 0 – 15cm from a 3 x 3m experimental plot developed in a farmland in Koroama community. Five sampled points, in the form of flat beds A, B, C, D and E respectively were randomly selected. Sampled beds A to D were simulated (contaminated) with 2.25kg of crude oil. The objective is to simulate conditions of a major crude oil spill. The crude oil contaminated soil samples were then allowed to condition for 6 days before treatment with 2kg organic treatments like goat manure (GM), poultry droppings (PD) and the combination of goat manure and poultry droppings (GM & PD). Bed E was unpolluted and untreated (control A) while Bed D was crude oil impacted and untreated soil (control B). The study showed that the impact of crude oil on the soil affects both the physical properties of the soil. The study also showed that the sampled organic treatments were all effective in restoring the physical properties of the crude oil impacted soil. At the end of the study, GM showed the highest TPH degradation rate (62.1%) followed by PD (57.1%) and the least, the combination of GM & PD (52.0%). Hence, the application of GM, PD and the combination of GM & PD are highly recommended for bioremediation of crude of impacted soil with special preference to GM.